BETWEEN CIVIL LIBERTY AND NATIONAL SECURITY IN JAMES MCTEIGUE'S V FOR VENDETTA (2006): A SOCIOLOGICAL APPROACH - IRAWATI, YESI (2010)
The problem of the study is to reveal how the tension between civil liberty and national security is reflected in James McTeigue's V for Vendetta. The objectives of the study are to analyze the structural elements of the movie and to analyze the movie based on the sociological perspective. This study employs the qualitative method. The object of the study is V for Vendetta movie directed by James McTeigue. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie itself and the secondary data are script text and some references related to the research. The techniques of data collection are note-taking and image-capturing. The technique of data analysis is descriptive analysis. The results of the research shows the following conclusions. Firstly, based on the structural analysis, the structural elements of V for Vendetta movie is connecting to each other to a whole unity that cannot be separated one another in order to support each other. Secondly, based on the sociological analysis it shows there is tension between civil liberty and national security in government system. V for Vendetta movie criticizes the totalitarian government of England. V for Vendetta proposes that government should give justice and freedom of their people.